2018
DOI: 10.1007/s10460-018-9886-0
|View full text |Cite
|
Sign up to set email alerts
|

Doing but not knowing: how apple farmers comply with standards in China

Abstract: Are public and private standards affecting farmer knowledge and moving farm practices toward food safety and environmental sustainability in China? We surveyed a total of 355 apple farmers, involved in chains supplying a diversity of retailing points, including supermarkets. Using a multivariate regression model, we find no measurable evidence that the certification schemes of farm bases and agribusiness companies lead to improved apple growers' knowledge regarding pest and disease management. The behavioral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Moreover, Ding et al. (2018) examined the food safety problem from the producer side and showed that apple farmers in China simply follow the directions of their farm‐based leaders without understanding the meanings of food safety standards and certifications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ding et al. (2018) examined the food safety problem from the producer side and showed that apple farmers in China simply follow the directions of their farm‐based leaders without understanding the meanings of food safety standards and certifications.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, referring to nutrition research in the US, Fleischhacker et al [320] argued that "The coronavirus disease 2019 (COVID-19) outbreak has further laid bare these strains, including food insecurity, major diet-related comorbidities for poor outcomes from COVID-19 such as diabetes, hypertension, and obesity, and insufficient surveillance on and coordination of our food system" (p 721). The focus on health is also related to food safety, which is fairly addressed in the analyzed literature [322][323][324][325][326][327][328][329][330], especially concerning foodborne diseases [329].…”
Section: Society and Culturementioning
confidence: 99%
“…Demographic variables such as age, education, and the membership in farmer organizations were found to influence farmers’ decisions ( Annor et al, 2016 , Ganpat et al, 2014 , Holzapfel and Wollni, 2014 , Kersting and Wollni, 2011 , Kibet et al, 2018 , Marine et al, 2016 , Pandit et al, 2017 , Parikhani et al, 2015 , Pongvinyoo et al, 2014 , Srisopaporn et al, 2015 , Suwanmaneepong et al, 2016 ). Other factors comprise institutional support ( Ganpat et al, 2014 , Holzapfel and Wollni, 2014 , Islam et al, 2012 , Kersting and Wollni, 2011 , Marine et al, 2016 , Parikhani et al, 2015 , Pongvinyoo, 2015 , Srisopaporn et al, 2015 ), infrastructure ( Kersting and Wollni, 2011 , Pandit et al, 2017 , Parikhani et al, 2015 ), economic impact variables ( Annor, 2018 , Aydın and Aktürk, 2018 , Ganpat et al, 2014 , Islam et al, 2012 , Jelsma et al, 2019 , Kersting and Wollni, 2011 , Kibet et al, 2018 , Marine et al, 2016 , Nirmala, 2015 , Ochieng et al, 2019 , Pongvinyoo et al, 2014 , Srisopaporn et al, 2015 , Suwanmaneepong et al, 2016 ), and knowledge and attitudes levels of producers ( Ding et al, 2019 , Kibet et al, 2018 , Nirmala, 2015 , Pandit et al, 2017 , Pongvinyoo, 2015 , Som et al, 2017 , Suwanmaneepong et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%